Prototipe Monitoring dan Controlling Lampu Ruangan Bersekat Kaca via Bluetooth Menggunakan Smartphone - Saputra, M. Yudis Hardi; Sulaiman, Sulaiman (MASALIQ, 2025)
Smart home technology continues to evolve, offering convenience and ease in managing electronic devices. One essential aspect of smart home systems is lighting control. This study aims to design and implement a prototype system for monitoring and controlling room lights separated by glass partitions using Bluetooth technology integrated with a smartphone. The research methodology includes hardware design using an Arduino Uno microcontroller, HC-05 Bluetooth module, and supporting sensors, as well as the development of an Android application as the user interface. The system is designed to control lights wirelessly, even in rooms with glass partitions. Tests were conducted to evaluate the reliability of the Bluetooth connection, system responsiveness, and ease of use of the application. The results show that the prototype successfully controlled lights within an optimal range of up to 10 meters, even with glass partitions. The developed smartphone application could display the real-time status of the lights and allowed users to switch them on or off with a response time of less than one second.in conclusion, this prototype provides an effective solution for lighting control in homes or workspaces, enhancing energy efficiency and offering greater convenience for users. This technology has the potential to be widely adopted in cost-effective and user-friendly smart home systems.